A PARAMETRIC STUDY TO ENHANCE THE DESIGN OF HYDROKINETIC TURBINE - Ng C.Y.; Maldar N.R.; Ean L.W.; Wong B.S.; Kang H.S. (American Society of Mechanical Engineers (ASME), 2024)
Many companies and governmental organizations have announced the aspiration to achieve Net Zero Carbon Emissions by 2050. Hence, electrification and low-carbon energy solutions are among the measures to reduce CO emissions. Seeing the fact that offshore platforms are in the middle of the ocean, and the ocean covers almost 80% of the earth surface, a high hydropower potential from the ocean with 29, 000 MW is extractable from Malaysia. Many of the oil and gas companies are eyeing for an alternative marine energy source for electrification of the offshore platforms such as solar, wind and wave. Unfortunately, many yet seen the potential of the marine current energy by Marine Hydrokinetic Turbine (MHKT). Indeed, the high predictability of the resources and maturity of the MHKT technology have strengthened the feasibility of the deployment of this device. Although the strength of the MHKT has been highlighted, but the deployment of the on-shelf MHKT devices in Malaysia region is still a challenge, mainly due to the slow current flow within the region. Acknowledging this limitation and insufficient depth found in Malaysian waters, the present research focusses on parametric study to maximize efficiency of an existing hydrokinetic turbine. The study is based on numerical simulations which are carried out using the CFD software. Prior to parametric study, performance of the conventional turbine is evaluated with the existing results of the manufacturers experimental testing reports. Thereafter, the effect of modifications on each of the structural parameters such as blade profile and number of blades arrangement is analyzed. For every structural parameter, the most optimal configuration was identified by comparing the obtained power performance variables. The enhanced design turbine achieved at the end of modifications is subjected to performance assessment for the same flow velocities as the conventional one. As a result, with the ocean current flow of 1 m/s, the enhanced design turbine can generate 268 watts of power, meanwhile 165 watts from the conventional one at the rate of 1.62 times higher. Copyright 2023 by ASME.